2008
DOI: 10.1021/cm800843s
|View full text |Cite
|
Sign up to set email alerts
|

Defect Chemistry of Yttrium-Doped Barium Zirconate: A Thermodynamic Analysis of Water Uptake

Abstract: Thermogravimetry has been used to evaluate the equilibrium constants of the water incorporation reaction in yttrium-doped BaZrO 3 with 20-40% yttrium in the temperature range 50-1000 °C under a water partial pressure of 0.023 atm. The constants, calculated under the assumption of a negligible hole concentration, were found to be linear in the Arrhenius representation only at low temperatures (e500 °C). Nonlinearity at high temperatures is attributed to the occurrence of electronic defects. The hydration enthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
159
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 28 publications
25
159
3
3
Order By: Relevance
“…Thereby, as a consequence of a physical artifact, ΔH H 2 O and ΔS H 2 O extracted from the curve may present inconsistent values in a wide temperature range. Not surprisingly, the resulting hydration entropies and enthalpies from 50-500 °C (-22 to -26 kJ/mol and -39 to -44 J/K.mol, respectively) of yttrium doped barium zirconate found by Yamazaki et al 52 were smaller in magnitude than those reported in the literature. As an example, at higher temperature range, 550-900 °C, the values of ΔH H 2 O and ΔS H 2 O reported by Kreuer et al 54 were -93.3 kJ/mol and -103.2 J/K.…”
Section: Incorporation and Proton Transport Mechanismsmentioning
confidence: 61%
“…Thereby, as a consequence of a physical artifact, ΔH H 2 O and ΔS H 2 O extracted from the curve may present inconsistent values in a wide temperature range. Not surprisingly, the resulting hydration entropies and enthalpies from 50-500 °C (-22 to -26 kJ/mol and -39 to -44 J/K.mol, respectively) of yttrium doped barium zirconate found by Yamazaki et al 52 were smaller in magnitude than those reported in the literature. As an example, at higher temperature range, 550-900 °C, the values of ΔH H 2 O and ΔS H 2 O reported by Kreuer et al 54 were -93.3 kJ/mol and -103.2 J/K.…”
Section: Incorporation and Proton Transport Mechanismsmentioning
confidence: 61%
“…19 Over a small change in proton concentration (the variation in conductivity recorded here is only about 10%) and under the approximation of ideal solution behavior, eqn (1) implies that the proton resistivity (inversely proportional to concentration) should display a power law factor of À B108 nm). 20 There are many factors that could explain a deviation from a power law factor of À 1 2 in undoped ceria even for bulk proton uptake, first amongst these being the low intrinsic oxygen vacancy concentration such that the effects of site saturation cannot be neglected.…”
Section: Electrical Characterizationmentioning
confidence: 74%
“…Sol-gel, polyacrylamide, combustion, coprecipitation are synthesis methods used to produce BZY powders with high sinterability to obtain dense compacts after sintering [16,18,[20][21][22][23]. The main advantage of the OPM over other methods is that it leaves no residues [33,34], which could otherwise promote deleterious effects on the proton conductivity.…”
Section: Comparison With Other Methods Of Synthesismentioning
confidence: 99%
“…Very recently, BZY protonic ceramic fuel cells with high power output have been reported using BZY solid electrolytes sintered with CuO sintering aid [19]. Wet-chemical routes have already been used to produce powder particles with higher sinterability to obtain pellets sintered at relatively low temperatures [16,18,[20][21][22][23][24]. A total proton conductivity of $0.01 S/cm at 450°C in a polycrystalline BZY20 sample produced by a sol-gel route was reported.…”
Section: Introductionmentioning
confidence: 99%